Quality analysis and metabolomic profiling of the effects of exogenous abscisic acid on rabbiteye blueberry - Yang, Hao; Han, Tianyu; Wu, Yaqiong; Lyu, Lianfei; Wu, Wenlong; Li, Weilin (Frontiers in Plant Science, 2023)
Blueberry is a characteristic berry fruit shrub of the genus Vaccinium in the Rhododendron family. The fruit is rich in anthocyanins and has a variety of nutritional and health functions. This study aimed to systematically study the effect of exogenous abscisic acid (ABA) application on ripening and metabolites in blueberry fruits. Blueberry fruit ripening was divided into six stages for further analysis.In this study, nontarget metabolomics was performed to demonstrate the effect on metabolite levels.The results showed that 1000 mg/L ABA significantly promoted fruit ripening and increased anthocyanin content. Moreover, exogenous ABA treatment can affect endogenous ABA levels and improve its antioxidant capacity. Important metabolites of the flavonoid pathway were detected, and the results showed that anthocyanin synthesis increased, and some other bioactive metabolite levels decreased. After comprehensive assessments, we believe that 1000 mg/L exogenous ABA application will have positive impacts on blueberry fruit quality and economic benefits.